Potentially toxic elements’ contamination of soils affected by mining activities in the Portuguese Sector of the Iberian Pyrite - Mourinha, Clarisse (2022)
Both sectors of the Iberian Pyrite Belt, Portuguese and Spanish, have been exploited since ancient times, but more intensively during and after the second half of the 19th century. Large volumes of polymetallic sulfide ore were extracted in open pits or in underground works, processed without environmental concerns, and the generated waste rocks and tailings were simply deposited in the area. Many of these mining sites were abandoned for years under the action of erosive agents, leading to the spread of trace elements and the contamination of soils, waters and sediments. Some of these mine sites have been submitted to rehabilitation actions, mostly using constructive techniques to dig and contain the contaminated tailings and other waste materials, but the remaining soil still needs to be treated with the best available techniques to recover its ecosystem functions. Besides the degraded physical structure and poor nutritional status of these soils, they have common characteristics, as a consequence of the pyrite oxidation and acid drainage produced, such as a high concentration of trace elements and low pH, which must be considered in the remediation plans. This manuscript aims to review the results from studies which have already covered these topics in the Iberian Pyrite Belt, especially in its Portuguese sector, considering: (i) soils’ physicochemical characteristics; (ii) potentially toxic trace elements’ concentration; and (iii) sustainable remediation technologies to cope with this type of soil contamination. Phytostabilization, after the amelioration of the soil’s properties with organic and inorganic amendments, was investigated at the lab and field scale by several authors, and their results were also considered.